Technical and Economic Analysis of the Supercritical Combined Gas-Steam Cycle - Marcin Jamróz; Marian Piwowarski; Paweł Ziemiański; Gabriel Pawlak (Energies, 2021)
Combined cycle power plants are characterized by high efficiency, now exceeding 60%. The record-breaking power plant listed in the Guinness Book of World Records is the Nishi-Nagoya power plant commissioned in March 2018, located in Japan, and reaching the gross efficiency of 63.08%. Research and development centers, energy companies, and scientific institutions are taking various actions to increase this efficiency. Both the gas turbine and the steam turbine of the combined cycle are modified. The main objective of this paper is to improve the gas-steam cycle efficiency and to reach the efficiency that is higher than in the record-breaking Nishi-Nagoya power plant. To do so, a number of numerical calculations were performed for the cycle design similar to the one used in the Nishi-Nagoya power plant. The paper assumes the use of the same gas turbines as in the reference power plant. The process of recovering heat from exhaust gases had to be organized so that the highest capacity and efficiency were achieved. The analyses focused on the selection of parameters and the modification of the cycle design in the steam part area in order to increase overall efficiency. As part of the calculations, the appropriate selection of the most favorable thermodynamic parameters of the steam at the inlet to the high-pressure (HP) part of the turbine (supercritical pressure) allowed the authors to obtain the efficiency and the capacity of 64.45% and about 1.214 GW respectively compared to the reference values of 63.08% and 1.19 GW. The authors believe that efficiency can be improved further. One of the methods to do so is to continue increasing the high-pressure steam temperature because it is the first part of the generator into which exhaust gases enter. The economic analysis revealed that the difference between the annual revenue from the sale of electricity and the annual fuel cost is considerably higher for power plants set to supercritical parameters, reaching approx. USD 14 million per annum. It is proposed that investments in adapting components of the steam part to supercritical parameters may be balanced out by a higher profit.